Legal Framework Analysis for CO2 Utilisation in Latvia - Terjanika Viktorija; Zarins Emils; Balode Lauma; Pubule Jelena (Environmental and Climate Technologies, 2022)
The ever-increasing amount of greenhouse gas emissions are forcing countries and the industrial sector in particular to develop ways to improve the manufacturing industry and reduce the amount of emissions created in compliance with the requirements of the European Green Deal initiative. However, all modifications must be under local laws and European directives. The purpose of this work is to analyse existing laws, regulations, and directives, both local and European, to identify limiting factors and factors that contribute to a more active introduction of systems for capturing, using, and reducing the amount of carbon dioxide created in production processes. The results of this analysis will determine the strengths and weaknesses of the local manufacturing sector and its ability to meet evertightening requirements.